ANALISA PARAMETER MESIN INJECTION MOLDING TERHADAP CACAT PRODUK HANDLE GRIP MENGGUNAKAN METODE TAGUCHI - Ervan Agus Siswoyo; Mochamad Mas'ud (Prodi Teknik Mesin Universitas Yudharta, 2022)
One of the causes of losses from the company is the presence of product defects in the production process, the cause of product defects that occur is suboptimal machine parameters. This study aims to analyze machine parameters so that product defects are reduced or minimal. In this study, the largest product defects were found, significant product defect factors, optimal combination of machine parameters and minimizing the defects of the company's products using the Taguchi Method with a Statistical Quality Control approach. The research data comes from the defects of the PT.X. Handle Grip machine product, from these data, it will then be processed using the Statistical Quality Control method, taguchi method, analysis of variants (ANOVA) and repair control. From statistical quality control analysis data, the biggest product defects can be obtained, namely heavy product defects of 4.74%. The analysis of the taguchi method can be obtained the best combination of parameters, namely an injection pressure of 52 bar, a cooling duration of 5 s and an injection temperature of 195oC. While the most influential factors on product defects based on ANOVA are injection pressure, injection temperature and finally cooling duration because F hit > F table with successive results of 403 > 3.04, 61 > 3.04 and 27 > 3.04. The results of the repair control were obtained better results, before the study of severe product defects of 4.74% dropped to 0.08%.